Essential elements: comprenhensive band method - Lautzenheiser, Tim. 1947- (Essential elements, 2004)
the following pages offer an ongoing sequential-learning curriculum, PLUS a library of additional benefits certain to offer every studente a positive pathway to musical excellence.